Cost of illness studies on reproductive, maternal, newborn, and child health: A systematic literature review - Sanjib Saha; Ulf-G. Gerdtham (Health Economics Review, 2013)
Background: The term 'reproductive, maternal, newborn, and child health (RMNCH)' describes an integrated continuum of health states which is central to Millennium Development Goals 4 and 5. While the burden of mortality and morbidity associated with RMNCH is well known, knowledge is still limited about the economic burden of RMNCH. Concrete evidence of cost of illness (COI) of RMNCH may help policy makers in supporting investment in RMNCH. Methods: A systematic literature search of COI studies was performed in electronic databases. The time frame for the analysis was January 1990 - April 2011. The databases checked were Medline (Pubmed), Embase and ECONbase, EconLit, the Cumulative Index to Nursing and Allied Health (CINAHL), the National Bureau of Economic Research, the Latin American and Caribbean Literature on Health Sciences Database (LILACS), and Popline. Furthermore, we searched working papers and reference lists of selected articles. Results: All the studies investigated address particular complications and issues of RMNCH, e.g., preterm birth, non-exclusive breastfeeding, and sexually transmitted diseases (STDs), but not RMNCH as an entire continuum. Most of the studies were conducted in high income countries, with limited data on low and middle income countries. The burden of disease is very high even for single complications. For example, the disease burden related to non-exclusive breastfeeding was given as 14.39 billion international dollars (ID) (2012, purchasing power parity) per year in the USA. Methodological differences in study design, costing approach, perspective of analysis, and time frame make it difficult to compare different studies. Conclusion: The continuum of RMNCH covers a large portion of the lifespan from birth through the reproductive age. From a methodological perspective, an ideal COI study would clearly describe the perspective of analysis and, hence, the cost items (direct or indirect), cost collection procedure, discounting, quality of data, time frame of analysis, related comorbidities, and robust sensitivity analysis for all the assumptions. Further research is needed to measure the economic impact of RMNCH, including identification of the most cost-effective policy and interventions for prevention, reduction, and elimination of the complications of RMNCH.
Keywords: 330; Cost of illness; Reproductive health; Maternal health; Breastfeeding; Preterm birth